2005
DOI: 10.1111/j.1365-2036.2005.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

New strategy of therapy for functional dyspepsia using famotidine, mosapride and amitriptyline

Abstract: SUMMARYBackground: In functional gastrointestinal (GI) disorders including functional dyspepsia (FD) and irritable bowel syndrome (IBS), there might be no small extent of contributions of psychosomatic factors. As a therapy for IBS patients, the effectiveness of antidepressants has been reported. Aim: In this study, we evaluated the efficacy of H 2 -receptor antagonist (famotidine) and 5-HT 4 receptor agonist (mosapride citrate). In addition, the effect of antidepressants was assessed as the second-step therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 21 publications
1
59
0
2
Order By: Relevance
“…Several studies showed that the anxiety, depression and somatoform disorders were the most common psychiatric problems found in patients with FD (Magni et al, 1987;Haug et al, 1994). Antidepressive drugs seem to be helpful in the treatment in some cases of FD patients (Mertz et al, 1998;Otaka et al, 2005). A meta-analysis published in 2005 demonstrated that anti-anxiety or anti-depressive drugs were effective in controlling symptoms in patients with FD (Hojo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that the anxiety, depression and somatoform disorders were the most common psychiatric problems found in patients with FD (Magni et al, 1987;Haug et al, 1994). Antidepressive drugs seem to be helpful in the treatment in some cases of FD patients (Mertz et al, 1998;Otaka et al, 2005). A meta-analysis published in 2005 demonstrated that anti-anxiety or anti-depressive drugs were effective in controlling symptoms in patients with FD (Hojo et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Ampliando a polêmica sobre o tema, outro estudo também recente (22) , mostrou efetividade da amitriptilina sobre os sintomas de DF. Para além da discussão sobre efetividade do tratamento, é importante que se considerem os efeitos colaterais dos psicofármacos (cólicas, náusea e diarréia no caso dos SSRIs pelo seu efeito procinético, e constipação, no caso dos antidepressivos tricíclicos).…”
Section: Discussionunclassified
“…In that study, amitriptyline was also effective for treating functional dyspepsia. 21 In addition, another US study in 90 children aged 8 to 17 years who had functional gastrointestinal disorders, reported that amitriptyline and placebo both gave a good response to therapy, but with no significant difference between amitriptyline and placebo after 4 weeks of treatment. 1 A study in adult patients with irritable bowel syndrome (IBS) showed that anxiety levels correlated with placebo analgesic effects.…”
Section: Discussionmentioning
confidence: 99%